2021
DOI: 10.3390/ma14092393
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Doped Biphasic Calcium Phosphate Powders: Dopant Release, Cytotoxicity and Antibacterial Properties

Abstract: Cytotoxicity and antibacterial properties associated with the dopant release of Cu-doped Biphasic Calcium Phosphate (BCP) powders, mainly composed of hydroxyapatite mixed with β-tricalcium phosphate powders, were investigated. Twelve BCP ceramics were synthesized at three different sintering temperatures (600 °C, 900 °C and 1200 °C) and four copper doping rates (x = 0.0, 0.05, 0.10 and 0.20, corresponding to the stoichiometric amount of copper in Ca10Cux(PO4)6(OH)2-2xO2x). Cytotoxicity assessments of Cu-doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…In a typical procedure, metaphysic cancellous bone tissues were collected during hip arthroplasty surgical procedures performed on patients who gave their consent beforehand for the use of their bones for research purposes. Then, they underwent multiple steps of treatment and culture, in order to collect the h-MSCs, as fully detailed by Jacobs et al 45…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a typical procedure, metaphysic cancellous bone tissues were collected during hip arthroplasty surgical procedures performed on patients who gave their consent beforehand for the use of their bones for research purposes. Then, they underwent multiple steps of treatment and culture, in order to collect the h-MSCs, as fully detailed by Jacobs et al 45…”
Section: Methodsmentioning
confidence: 99%
“…In a typical procedure, metaphysic cancellous bone tissues were collected during hip arthroplasty surgical procedures performed on patients who gave their consent beforehand for the use of their bones for research purposes. Then, they underwent multiple steps of treatment and culture, in order to collect the h-MSCs, as fully detailed by Jacobs et al 45 Prior to the cytotoxicity tests, the heterostructured NPs were sterilized by keeping them in an oven at 180 °C for 2 h. Then, h-MSCs cultured in minimum essential medium (MEM) were seeded in a 24-well plate, exposed to the nanopowders with a concentration of 1 mg mL −1 , and incubated at 37 °C for 3 or 7 days. MEM-cultured h-MSCs without powder were used as a control.…”
Section: In Vitro Cytotoxicity Testsmentioning
confidence: 99%
“…In addition, they reported that it had good adherence to bone marrow cells and maintained good cell viability. Therefore, they recommended it as a promising bioceramic for bone substitution and/or prosthesis coatings [ 109 , 110 ]. A study reported using graphene oxide copper nanocomposites for bone regeneration and revealed vascularized new bone formation [ 111 ].…”
Section: Copper Nanoparticles In Dental Materialsmentioning
confidence: 99%
“…Biphasic calcium phosphate (BCP) ceramics have been proved to promote ectopic bone formation after subcutaneous or muscle pouch implantation in rodents or larger animals (dog, goat, and sheep) [ 5 ]. In this model, BCP ceramics have excellent biocompatibility and osteo-inductive ability [ 6 , 7 ]. In addition, BCP has been reported to regulate the phenotype of macrophage, dendric cell, and T cell to recruit bone marrow mesenchymal stem cells (BMSCs) and enhance osteogenic differentiation of BMSCs [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%